Asymmetric information in the labor market, immigrants and contract menu - Saibal Kar; Bibhas Chandra Saha (Institute for the Study of Labor (IZA), 2011)
Immigrant workers and their labor force participation in host countries have received critical attention in all concerned disciplines, principally owing to its strong implications for well-being of natives. The ageing population in many rich countries and several related and unrelated issues including global integration, pension provisions or security threats keeps immigration under continuous impact evaluation. However, of the several studies that dealt with patterns and consequences aspects of labor migration, only a handful discusses asymmetric information across transnational labor markets despite agreement that a standardized screening mechanism is unavailable. At the same time, several empirical studies show that immigrants are proportionally overrepresented in self-employment, vis-à-vis natives of equivalent skill levels. We try to explain this phenomenon based on asymmetric information in the host country labor market. We focus on the design of a contract menu by the employers, which when offered to a mixed cohort of immigrants facilitates self-selection in favor of paid employment or the outside option of self-employment/entrepreneurship. We also discuss countervailing incentives among the mixed cohort.
urn:nbn:de:101:1-201104113815
Keywords: D82; J23; J24; J41; J61; 330; immigrants; asymmetric information; labor contracts; self-employment; incentive compatibility; Migranten; Berufswahl; Asymmetrische Information; Arbeitsvertrag; Selbstständige; Anreizvertrag; Theorie